(3GdChGQb GdJLGQjI hGdEadGS habG dbGfhf GdJLGQI GdLOjO Qbe (B17 (3dSfI (B1999s - (3Ydj(B, (3GdHGQhOjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI GdLOjOI(B,s, 2004)
(3GdJYQja HGdChQGb GdJLGQjI hCfhGYgG hhXGFagG, GdCSS GdJj Jbhe YdjgG bhGYO bGfhf GdUQa, JTQjY GdChQGb GdJLGQjI, GfTGA GdceHjGdI, JOGhd GdceHjGdI, JOGhd GdceHjGdI, VeGfGJ GdhaGA HGdceHjGdI, GdhaGA HGdceHjGdI, GdSbhW hGdJbGOe, CKQ GdJYGed HGdceHjGdI, GdSbhW hGdJbGOe, CKQ GdJYGed HGdceHjGdI aj GdOjf GdCUdj, GdSfO GdCOfi (B((3Ch ddCeQ(B)(3, GdGadGS, JaGOj GdJGLQ ddJGLQ dTgQ GadGSg, TgQ GdGadGS, GdBKGQ GdeJQJHI Ydi Mce GdGadGS, GdBKGQ GdeJQJHI Ydi Mce GdGadGS, eUjQ GdJadjSI(B.s
Keywords: (3GdChQGb GdJLGQjI(B- (3GdEadGSs; (3GdChQGb GdfbOjIs; (3GdGadGSs